Complex interspecific and intersexual patterns of wing design in Heliconius butterflies - Luis Mendoza-Cuenca (Nota Lepidopterologica)
In butterflies, interspecific and intersexual variation in wing design morphology modifies aerodynamic efficiency and individuals’ flight costs. Wing design involves traits like wing shape and size, which determine flight performance and behavioral ability, which determine individuals’ flight performance and behavioural capacity under their ecological and reproductive requirements. In this context, evolutionary adjustments in wing shape are expected to be adaptive responses to specific flight requirements that allow acrobatic maneuvers to evade predators, for females reduce the costs of takeoff and flight maintenance linked to the additional weight of eggs and ovarioles, or for males improve flight efficiency during costly and long courtship displays. Here, the intra- and interspecific variation in wing shape of butterflies in the genus Heliconius Kluk, 1780. was analyzed using geometric morphometrics techniques, as well as its association with i) intersexual differences in flight requirements, ii) mating system, and iii) the presence of co-mimic pairs. The results highlight the relevance of sexual selection associated with mating systems and life history traits as the predominant force that promotes the patterns of sexual dimorphism in wing shape observed in Heliconius. In this context, both sexes exhibit contrasting wing shapes according to the mating strategies (i.e. pupal mating vs courtship species). However, there are also remarkable intersexual wing shape differences, potentially associated with the pressures that impose egg production on females. Additionally, Heliconius species that form co-mimic pairs also show a strong wing shape convergence despite belonging to different subclades. The results highlight the complexity of traits involved in the evolutionary designs of wings in Lepidoptera.